2010
DOI: 10.1002/pros.21265
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2–ERG gene fusion prevalence and class are significantly different in prostate cancer of caucasian, african‐american and japanese patients

Abstract: The prevalence and class of TMPRSS2-ERG are significantly different in PCa of Caucasian, African-American, and Japanese patients. Future studies of the molecular pathways implicated in TMPRSS2-ERG gene fusion may shed light on the disparity in prevalence and mortality of PCa among different ethnic groups and help design better prevention and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
204
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(232 citation statements)
references
References 30 publications
20
204
6
2
Order By: Relevance
“…Importantly, the association of PTEN loss with lethal events among ERG fusion-negative tumors was much stronger than that seen for PTEN loss considered without ERG status, and this association remained strong even when considering tumors with heterogeneous PTEN loss. Finally, white men primarily comprise our cohort (97%), so our results may not be generalizable to other racial/ethnic groups, in which ERG expression and PTEN loss may be less frequent (45)(46)(47)(48)(49)(50).…”
Section: Articlementioning
confidence: 99%
“…Importantly, the association of PTEN loss with lethal events among ERG fusion-negative tumors was much stronger than that seen for PTEN loss considered without ERG status, and this association remained strong even when considering tumors with heterogeneous PTEN loss. Finally, white men primarily comprise our cohort (97%), so our results may not be generalizable to other racial/ethnic groups, in which ERG expression and PTEN loss may be less frequent (45)(46)(47)(48)(49)(50).…”
Section: Articlementioning
confidence: 99%
“…[13][14][15] The TMPRSS2-ERG gene fusion is the principle genomic alteration and a characteristic signature in approximately half of all prostate cancers. 14,[16][17][18][19][20][21][22][23] ERG regulates matrix metalloproteinases, thus influencing extracellular matrix remodeling and the invasive potential of malignant cells. [24][25][26][27] PTEN is among the most commonly mutated tumor suppressor genes in human cancer.…”
mentioning
confidence: 99%
“…13 Such findings are consistent with previous reports on PCa patients in China, 14 as well as those in Japanese and Korean populations. [15][16][17] Two novel gene fusions, CTAGE5-KHDRBS3 and USP9Y-TTTY15, occurred frequently in our patient cohort; 13 further validation in a larger and multicentre population is warranted. These differences may be further utilized in exploring the unique Chinese mechanism upon tumour onset and progression, as a study has confirmed a possible alternative path of carcinogenesis in gene fusion and PTEN inactivation.…”
Section: Gene Fusionmentioning
confidence: 89%